Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Pembelian Jasa pada Ekspedisi JNE : Studi Kasus PT JNE Tomang, Jakarta Barat - Edo Maharatma Rosandy; Heni Rohaeni; Indah Rizki Maulia (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to test whether Service Quality and Promotion influence Purchasing Decisions. The method used in this research is a quantitative method. The population in this research is consumers of PT JNE Tomang, West Jakarta. The sample used in this research used Accidental Sampling with the Slovin formula calculation, namely 100 respondents were obtained. Data analysis using Smart PLS 3.0 The analysis method used is descriptive analysis, validity test, reliability test, r-Square test, f-square test and hypothesis test. The research results show that service quality has no effect on purchasing decisions with t-statistics = 1.439 < t-table = 1.978, but there is a positive and significant influence between promotions on purchasing decisions with the calculated value of t-statistics = 4.781 > t-table = 1.978. This shows that the better the promotion given, the better the decision to purchase services on JNE expeditions.